2012
DOI: 10.1186/2049-6958-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Prominent features of platelet count, plateletcrit, mean platelet volume and platelet distribution width in pulmonary tuberculosis

Abstract: BackgroundWe aimed to investigate the relation of platelet count (PLT) and plateletcrit (PCT), mean platelet volume (MPV) and platelet distribution width (PDW) with other acute phase reactants and radiological extent in pulmonary tuberculosis (PTB).MethodsOne hundred patients with PTB (Group 1), 50 patients with community-acquired pneumonia (Group 2) and 28 healthy control individuals (Group 3) were included in this analytic study.ResultsWBC (White Blood Cell), ESR (Eritrocyte Sedimentation Rate), CRP (C-React… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 11 publications
6
39
2
1
Order By: Relevance
“…Most often, it was observed that patients with severe tuberculosis had anemia, elevated ESR, and thrombocytosis [18]. Other studies also reported that patients with advanced pulmonary TB demonstrated anemia, leukocytosis, elevated ESR, and thrombocytosis [5,[19][20][21][22][23]. In our study, we found that NLR, RDW, ESR, and CRP values are higher in patients with advanced stage PTB when compared to patients with mild to moderate PTB.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Most often, it was observed that patients with severe tuberculosis had anemia, elevated ESR, and thrombocytosis [18]. Other studies also reported that patients with advanced pulmonary TB demonstrated anemia, leukocytosis, elevated ESR, and thrombocytosis [5,[19][20][21][22][23]. In our study, we found that NLR, RDW, ESR, and CRP values are higher in patients with advanced stage PTB when compared to patients with mild to moderate PTB.…”
Section: Discussionsupporting
confidence: 47%
“…Patients with PTB were classified according to the extent of disease evident on chest radiography: stage 1 was minimal to mild disease, stage 2 was moderate disease, and stage 3 was advanced disease [5,16,17]. Lesions were considered minimal if there was no evidence of cavitation and the lesions were of slight to moderate density located above the second chondrosternal junction.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 82 patients with pulmonary tuberculosis found an elevated MPV compared to controls and also a correlation between MPV and radiological disease [20]. When compared to patients with bacterial pneumonia, pulmonary tuberculosis patients showed higher MPV and platelet counts [3]. However, other studies have found contrasting results.…”
Section: Discussionmentioning
confidence: 80%
“…There is evidence that suggests that MPV behaves differently in bacterial infections compared to other etiologies, and that pulmonary tuberculosis is associated with changes in platelet counts and MPV [2,3]. We hypothesized that these parameters could be of use in the differential diagnosis of bacterial (BM) and tuberculous meningitis (TBM).…”
Section: Introductionmentioning
confidence: 99%